ENHANCING STUDENTS' PRONUNCIATION SKILL USING CARTOON VIDEO IN AN EFL CLASSROOM - Ni Luh Gede Dita Indah Sari; I Dewa Gede Rat Dwiyana Putra; I Putu Andre Suhardiana (UHN IGB Sugriwa Denpasar, 2024)
This research aims to identify the best implementation of cartoon video to improve students’ pronunciation skill and their perception of cartoon video in learning pronunciation. This Classroom Action Research (CAR) cyclic procedure consist of four stages, namely: planning, action, observation, and reflection. The technique of data collection in this research were observation, test, and questionnaire. The finding showed that the implementation of cartoon video in an EFL classroom, which consider the learning system, speech rate of the video, and the amount of pronunciation practice, was able to improve students’ pronunciation skill. It was indicated by the percentage of students’ activity rate that reach more than 75%, the percentage of students who passed the minimum criteria of mastery learning (KKM) reach more than 75%, the average of pronunciation test score reach more than 70. Students shows a strong positive perception on the quality of the cartoon video, the ease of use of the cartoon video, and also the usefulness of the cartoon video. Based on the finding, the teacher should pay attention to these three factors: learning system, speech rate of video, and the amount of students’ pronuciation practice when teaching pronunciation using cartoon video.